Pregnancy outcomes in inflammatory bowel disease patients treated with vedolizumab, anti‐TNF or conventional therapy: results of the European CONCEIVE study. Issue 1 (6th November 2019) - Moens, Annick; van der Woude, C. Janneke; Julsgaard, Mette; Humblet, Evelien; Sheridan, Juliette; Baumgart, Daniel C.; Gilletta De Saint‐Joseph, Cyrielle; Nancey, Stéphane; Rahier, Jean‐François; Bossuyt, Peter; Cremer, Anneline; Dewit, Sophie; et al.
Summary: Background: Women with inflammatory bowel diseases (IBD) often receive biologicals during pregnancy to maintain disease remission. Data on outcome of vedolizumab‐exposed pregnancies (VDZE) are sparse. Aims: To assess pregnancy and child outcomes of VDZE pregnancies and to compare these results to anti‐TNF exposed (TNFE) or both immunomodulatory and biologic unexposed (CON IBD) pregnancies. Methods: A retrospective multicentre case‐control observational study was performed. Results: VDZE group included 79 pregnancies in 73 IBD women. The TNFE and CON IBD group included 186 pregnancies (162 live births) in 164 IBD women and 184 pregnancies (163 live births) in 155 IBD women, respectively. At conception, cases more often had active disease ([VDZE: 36% vs TNFE: 17%, P  = .002] and [VDZE: 36% vs CON IBD: 24%, P  = .063]). No significant difference in miscarriage rates were found between groups (VDZE and TNFE: 16% vs 13%, P  = .567; VDZE and CON IBD: 16% vs 10%, P  = .216). In live‐born infants, median gestational age and birthweight were similar between groups. Median Apgar score at birth was numerically equal. Prematurity was similar in the VDZE group compared to the control groups, even when correcting for disease activity during pregnancy. The frequency of congenital anomalies was comparable between groups as were the percentages of breastfed babies. During the first year of life, no malignancies were reported and infants' infection risk did not significantly differ between groups. Conclusion: No new safety signal was detected in VDZE pregnancies although larger, prospective studies are required for confirmation.